The Mechanism of Good Corporate Governance, Financial Performance, and Stock Returns on Company Value - Anto Andreawan; Muhammad Husni; M. Fadly Syahputra (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2026)
This study aims to examine the effects of good corporate governance (GCG), financial performance, and stock returns on firm value among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017–2019 period. Employing an exploratory research design, this analysis utilizes multiple linear regression and moderation regression analysis (MRA). The study population consists of manufacturing companies, with a sample of 142 companies selected due to their diverse subsectors, large production scale, and significant capital requirements, which demand effective asset management to generate high returns. Corporate value is measured using Tobin’s Q. The results indicate that GCG (board size and audit committee size), financial performance (ROA, NPM, PER), and stock returns simultaneously and significantly influence corporate value. Partially, all variables studied namely ROA, NPM, PER, board size, audit committee size, and stock returns have a significant influence on firm value. The MRA results indicate that the interaction between the board of commissioners and financial performance (NPM, PER) significantly influences firm value, but this is not the case for the interaction between the board of commissioners and ROA. Similarly, the interaction between the audit committee and NPM and PER significantly influences firm value, while the interaction between stock returns and ROA, NPM, and PER also demonstrates a significant influence.